Risk stratification of EGFR+ lung cancer diagnosed with panel-based next-generation sequencing. (October 2020) - Christopoulos, P.; Kirchner, M.; Roeper, J.; Saalfeld, F.; Janning, M.; Bozorgmehr, F.; Magios, N.; Kazdal, D.; Volckmar, A.L.; Brückner, L.M.; Bochtler, T.; Kriegsmann, M.; et al.
Highlights: EGFR variant, TP53 and brain status together predict survival in EGFR + NSCLC (ENS). Co-mutations beyond TP53 are rare and their clinical significance remains unclear. The ENS is a practical and reproducible baseline risk stratification of EGFR + NSCLC. Abstract: Objective: Panel-based next-generation sequencing (NGS) is increasingly used for the diagnosis of EGFR -mutated non-small-cell lung cancer (NSCLC) and could improve risk assessment in combination with clinical parameters. Materials and methods: To this end, we retrospectively analyzed the outcome of 400 tyrosine kinase inhibitor (TKI)-treated EGFR + NSCLC patients with validation of results in an independent cohort (n = 130). Results: EGFR alterations other than exon 19 deletions (non-del19), TP53 co-mutations, and brain metastases at baseline showed independent associations of similar strengths with progression-free (PFS hazard ratios [HR] 2.1–2.3) and overall survival (OS HR 1.7–2.2), in combination defining patient subgroups with distinct outcome (E GFR + N SCLC risk S core, "ENS", p < 0.001). Co-mutations beyond TP53 were rarely detected by our multigene panel (<5%) and not associated with clinical endpoints. Smoking did not affect outcome independently, but was associated with non-del19 EGFR mutations (p < 0.05) and comorbidities (p < 0.001). Laboratory parameters, like the blood lymphocyte-to-neutrophil ratio and serum LDH, correlated with the metastatic pattern (p < 0.01), but had no independent prognostic value. Reduced ECOG performance status (PS) was associated with comorbidities (p < 0.05) and shorter OS (p < 0.05), but preserved TKI efficacy. Non-adenocarcinoma histology was also associated with shorter OS (p < 0.05), but rare (2–3 %). The ECOG PS and non-adenocarcinoma histology could not be validated in our independent cohort, and did not increase the range of prognostication alongside the ENS. Conclusions: EGFR variant, TP53 status and brain metastases predict TKI efficacy and survival in EGFR + NSCLC irrespective of other currently available parameters ("ENS"). Together, they constitute a practical and reproducible approach for risk stratification of newly diagnosed metastatic EGFR + NSCLC.